Safety of l‐threonine produced by fermentation with Escherichia coli CGMCC 11473 as a feed additive for all animal species. (6th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: The l ‐threonine under assessment is produced by fermentation with a genetically modified strain of Escherichia coli and it is intended to be used as a nutritional additive for all animal species. In 2017 the Panel on Additives and products or Substances used in Animal Feed (FEEDAP) of EFSA issued an opinion on the safety and efficacy of the product. In that assessment, the Panel could not conclude on the safety of the additive for the target species, consumers and the environment due to the lack of data regarding the characterisation of the production strain and the resulting product. The applicant provided additional data on the identity of the production strain, the genetic modification, the susceptibility to antibiotics and the absence of cells and recombinant DNA of the production strain in the final product. The recipient strain is safe and the genetic modification does not raise concerns. Moreover, viable cells or DNA of the production strain were not detected in the final product. With this new information the FEEDAP Panel concluded that l ‐threonine produced by E. coli CGMCC 11473 is safe for the all animal species, the consumers and the environment. The FEEDAP Panel could not conclude on the potential of the additive to be irritant to skin and eyes or on the skin sensitisation potential. It was concluded that there is a risk of exposure to endotoxins by inhalation for persons handling the additive.